Esthetic and Functional Rehabilitation of a Patient with Amelogenesis Imperfecta Using Adhesive and Non-Invasive Techniques: A Case Report - Priyake D Palipana; Achini Adikari (Wolters Kluwer Medknow Publications, 2022)
Introduction: Limited evidence is available on adhesive dentistry in the management of amelogenesis imperfecta (AI). The presentation, the conservative management with adhesive techniques, and the outcome of hypoplastic AI are discussed. Case Report: Autosomal dominant, hypoplastic AI was diagnosed, on a 36-year-old woman, presented with unesthetic teeth and a history of frequent decay with subsequent complications. Following the hygienic phase, stabilization of caries and root canal treatment (RCT) were done. Coronal restoration of endodontically treated teeth and light-cured direct composite veneering were done in the restorative phase. Surveyed crowns, mucosa-borne partial denture, and a resin-bonded bridge were prescribed in the prosthetic phase. The patient was pleased with the improved masticatory ability and esthetics. Discussion: A stepwise least invasive, yet esthetically acceptable treatment options based on adhesive techniques are successful in hypoplastic AI.